Prototype Development of a Real-Time Monitoring System Based on Android and Cloud Database for Textile Non-Thermal Plasma Treatment - Fadil Abdullah; Valentinus Galih Vidia Putra; Siti Nur Hamidah; Hafizah Aprilia (Journal of Advances in Information and Industrial Technology, 2025)
The textile modification process using plasma treatment requires accurate monitoring of gas species generated during operation; however, no system is currently available to measure these gas concentrations in real time. To address this gap, this study develops a plasma gas monitoring system for textile material modification, using experimental data obtained from laboratory tests conducted in 2024. The research employs a practical prototyping approach consisting of four stages: requirement identification, system design, prototype construction, and performance validation. The system is designed to continuously record plasma-generated gas concentrations and store the data in an internet-based database. The prototype consists of two main components: (1) a sensing unit built on an Arduino Uno microcontroller integrated with DHT-11 and MQ-131 sensors for measuring temperature, humidity, and ozone concentration, and (2) a data management platform using Google Spreadsheet connected to a mobile application to enable real-time monitoring and control. Evaluation results show that the monitoring tool achieved a Mean Absolute Error (MAE) of 0.6625 ppm, indicating that the system provides reasonably accurate measurements for initial validation. As this assessment is preliminary, future studies should employ a larger dataset to increase statistical robustness and further verify system performance. Overall, the findings contribute to the development of an accessible, Android-based plasma treatment monitoring system capable of supporting real-time monitoring in textile material modification applications.